The Effect of Multiple Injections of Ranibizumab on Retinal Nerve Fiber Layer Thickness in Patients with Age-Related Macular Degeneration. (January 2015) - Demirel, Sibel; Batıoğlu, Figen; Özmert, Emin; Erenler, Feyza
Abstract Purpose: To evaluate the effects of multiple intravitreal injections of ranibizumab on retinal nerve fiber layer (RNFL) thickness in patients with wet age-related macular degeneration (AMD). Methods: This observational, comparative study included patients with 10 or more total ranibizumab injections and involved the measurement of RNFL thickness at baseline. Twenty-nine eyes of 29 consecutive patients were evaluated via intraocular pressure (IOP) and measurements of the total and nasal RNFL thicknesses at the initial and final follow-up by using optical coherence tomography. The RNFL thickness values of the fellow eyes and 27 healthy eyes were used as the control group. The mean total and nasal RNFL thicknesses of the injection group were compared with those of the other two groups. At each visit, at every three injections, the IOP values of the study group were recorded and compared. The relationship between the number of injections and the mean RNFL thickness was assessed. Results: The mean number of injections was 13.88 ± 3.81 (10–24). The mean RNFL thickness of the injection group was 92.3 ± 7.7 μm at baseline and 92.46 ± 8.1 μm at the last follow-up (p = 0.7). There were no statistically significant differences between the mean total and nasal RNFL thicknesses of the eyes with injections and the fellow eyes with no injections (p = 0.379, p = 0.897, respectively) or between those with injections and the healthy control group (p = 0.159, p = 0.273, respectively). There were no correlations between the number of injections and the mean total and nasal RNFL thicknesses (p = 0.854, p = 0.25, respectively). There was no statistical difference between the initial and final IOPs (p = 0.760). Conclusion: Long-term treatment with anti-vascular endothelial growth factor (VEGF) agents did not lead to significant changes in RNFL thickness in a patient population with wet AMD. Chronic therapy with intravitreal anti-VEGF agents does not appear to adversely affect RNFL thickness.